2017
DOI: 10.1039/c7cc01973d
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazine-fused isoindigo: a new building block for polymer solar cells with high open circuit voltage

Abstract: Pyrazine-fused isoindigo (PzIIG) was designed and synthesized as a novel electron acceptor to construct two D-A conjugated polymers, PzIIG-BDT2TC8 and PzIIG-BTT2TC10. Both the polymers were successfully applied in polymer solar cells, and the PzIIG-BDT2TC8 based solar cell device exhibited a PCE of 5.26% with a high V over 1.0 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…As shown in Figure a, ν­(CO) of DR 9 shifts toward lower wavenumbers, while δ­(N–H) and ν ar (CC) of DR 9 shift toward higher wavenumbers after DR 9 diffusing into the PET film. It has been previously reported that there are intramolecular hydrogen bonds between the amino group and the carbonyl group of the anthraquinone dye molecule, and the molecular planarity is thus enhanced. In addition, when the hydrogen bond is formed, ν­(CO) and ν­(N–H) bands will shift to lower wavenumbers, while the δ­(N–H) band is just the opposite, moving to higher wavenumbers. Under such a circumstance, the shift of the bands of ν­(CO) and δ­(N–H) would indicate the strengthening of intramolecular hydrogen bonds of DR 9 with diffusion, which consequently results in the enhancement of the planarity of the DR 9 molecules and makes it easier for DR 9 molecules to diffuse into the PET film.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a, ν­(CO) of DR 9 shifts toward lower wavenumbers, while δ­(N–H) and ν ar (CC) of DR 9 shift toward higher wavenumbers after DR 9 diffusing into the PET film. It has been previously reported that there are intramolecular hydrogen bonds between the amino group and the carbonyl group of the anthraquinone dye molecule, and the molecular planarity is thus enhanced. In addition, when the hydrogen bond is formed, ν­(CO) and ν­(N–H) bands will shift to lower wavenumbers, while the δ­(N–H) band is just the opposite, moving to higher wavenumbers. Under such a circumstance, the shift of the bands of ν­(CO) and δ­(N–H) would indicate the strengthening of intramolecular hydrogen bonds of DR 9 with diffusion, which consequently results in the enhancement of the planarity of the DR 9 molecules and makes it easier for DR 9 molecules to diffuse into the PET film.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer P88 contained an acceptor PzIIG, having the 1,4-pyrazine ring as the bridge between two indolinones. 100 The PzIIG had little difference in the HOMO/LUMO energy levels relative to those of the IID counterpart but gave a dense and ordered packing state, whose p-p stacking distance was as small as 3.29Å (Fig. 8b), due to the formed N/H hydrogen bond between 1,4-pyrazine and indolinone.…”
Section: Chemical Science Reviewmentioning
confidence: 98%
“…[ 50 ] As shown in Figure 1f, some center‐inserted isoindigo derivatives can be synthesized by the Knoevenagel condensation with oxindole as a precursor. [ 51–53 ] Wan's group synthesized a isoindigo derivative using an oxindole‐based precursor. Inspiringly, the alkylation and condensation are carried out in a one‐pot reaction in this method (Figure 1g).…”
Section: Synthetic Tactics Of Isoindigo‐derived Monomers and Polymersmentioning
confidence: 99%
“…[ 51 ] For P141 , pyrazine was inserted into isoindigo. [ 53 ] In addition to improving the planarity by the intramolecular hydrogen bonding, this fragment also enhanced the electron‐withdrawing ability of the acceptor unit. The fabricated OPVs exhibited a PCE of 5.26% with a V OC higher than 1 V. [ 53 ] Alternatively, Yue and co‐workers synthesized P43 using peripherally extended isoindigo derivative M23 .…”
Section: Modification Strategies Of Isoindigo‐derived Polymer For Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation